Relationship between Childbirth Experience and Childbearing Attitude: A Systematic Review and Meta-Analysis - Dolatian, Mahrokh; Ghavidel, Nooshin; Bagherinia, Marzieh; Bahrami, Giti; Mahmoodi, Danial; Esmaelzadeh- Saeieh, Sara; Yazdkhasti, Mansoureh; Akbari Kamrani, Mahnaz; Hosseinpour, Kimia; Mahmoodi, Zohreh (Advances in Nursing & Midwifery, 2024)
Abstract Introduction: Childbirth is an experience that remains in the mind for years and can have many short-term and long-term consequences for women’s health and reproductive attitudes. The present study was conducted to assess the relationship between childbirth experience and childbearing attitude. Methods: A search was carried out in PubMed, Web of Science, Scopus, and search engine: Google Scholar using MeSH terms and their proper combinations via Boolean operators "AND" and "OR" operators according to each database over the years 2000 to 2022. We included published papers provided that they fulfilled all of the following criteria: Observational study (cross-sectional, case-control, and cohort), English language, investigating the relationship between pregnancy experience (positive/negative) and childbearing attitude (using questionnaires), and the participants being of reproductive age. The meta-analysis results were reported as odds ratio (OR) with a 95% confidence interval (CI). The I2 index and Cochran's Q test were used to assess the heterogeneity of the studies. The quality of the included studies was evaluated using the Newcastle-Ottawa Scale (NOS). Egger's and Begg's tests were performed to evaluate publication bias, and the leave-one-out approach was used for sensitivity analysis. R package Meta was used for the meta-analysis. Results: A total of 13,057 articles entered the screening and selection phase, and after implementing the main steps of the systematic review, six articles were ultimately accepted for the final review based on the eligibility criteria. The results of the metaanalysis of four studies with a high level of methodological quality demonstrated that people with negative or traumatic experiences in a previous pregnancy had 15% less positive attitude toward childbearing (OR=0.85; 95% CI: 0.50 to 1.45; I2=93%; Chi2=44.06, df=3, p < 0.01). Publication bias had no effect on the results obtained, and there was no significant bias in the publication of the results. Conclusions: Given the association observed in the current study, the mother's negative childbirth experience can play a deterrent role in her future fertility-related decisions. In their plans to promote high-quality caregiving, healthcare providers should also focus on this component to improve women's childbirth experiences.